Life Sciences in the 21st Century: New Ideas and Their Effects - V Basil Hans (International Journal of Bioinformatics and Computational Biology, 2026)
The life sciences have made huge strides in the 21st century, thanks to quick progress in genomics, biotechnology, and computational biology. New technologies like gene editing, personalised medicine, and synthetic biology have changed the way we think about living systems and changed the way we do things in healthcare, farming, and managing the environment. Combining big data and artificial intelligence has sped up discoveries even further, making it possible to provide accurate diagnoses and focused treatments. These developments have had a big impact on many areas, including disease prevention and treatment, food security through genetically altered crops, and finding long-term answers to global problems like climate change and loss of biodiversity. But these changes also bring up serious moral, social, and legal issues, such as worries about genetic privacy, biosecurity, and fair access to new technology. This article talks about the most important new ideas that are changing the life sciences today and how they are changing society. It stresses the necessity for responsible research and global cooperation to make sure that scientific progress helps everyone.
Keywords: Genomics; Life sciences; Personalised Medicine; Sustainability; Synthetic Biology; and bioethics; artificial intelligence; biotechnology